Implementasi Maqashid Syariah di Toko Sewu Satus Kecamatan Lohbener Kabupaten Indramayu - Fadhli Suko Wiryanto; Isti’anah Rizqullah (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Islam has taught everything, including teaching about moral-based mechanisms in the maintenance of justice and social welfare in the field of economics. with the field research method implemented in the distribution of income and wealth of the basic food business at the Sewu Satus Shop, Lohbener District, Indramayu Regency, maqasid sharia emphasizes Fulfillment of family needs, must prioritize if there is debt, which must be prioritized is paying zakat if it has fulfilled the nishab and haul, funds musaadah and so on are applied by Toko Sewu Satus for equal distribution of income and wealth and proper allocation, both mandatory and sunnah, for the creation of income equality among others, starting from the distribution of family coverage, so that there is no accumulation of wealth only for them but allocation has been made. By holding the principle of avoiding the element of usury capital. In order to create a fair, honest and equitable distribution system, Islam stipulates positive and prohibitive actions. Positive actions include zakat, infaq, alms, while prohibitive actions include the prohibition of usury.